Tabot Festival: Shi'a Tradition Within The Sunni Community Of Bengkulu City On Sociology Of Islamic Law Perspective - Fahimah, Iim; Jafar, Wahyu Abdul (AL-ISTINBATH : Jurnal Hukum Islam, 2020)
The purpose of this research is to describe the Tabot festival, a legacy of the Shia tradition but still exists and held continuously in the Sunni community of Bengkulu City. This festival is a manifestation of love for Sayidina Husen bin Ali from people of Bengkulu. However, even though the purpose of this Tabot is useful, there are still some people who are questioning the legality of Tabot’s law because it is strongly suspected that Shiites brought this festival to the Bengkulu. This research was held to answer the legality of Tabot’s law, which is still being disputed by the Sunni community. Through this study, the researcher explained in detail the Tabot legal issues through the sociology of Islamic law Perspective. This research is categorized as field research, and the approach used in this research is the sociology of Islamic law. Data collection techniques used were interview and documentation techniques. After an in-depth study, it was concluded that the Tabot Festival was accepted by the Sunni community, but there are a few sets of events that need to be improved, because it was considered to violate Shari'ah. The allowed event series are Duduk Penja, Meradai, Menjara/Mengandun, Arak Penja, Mengarak Penja Bersurban, Gam, and Arak Gendang. There are two series of Tabot programs that need to be improved, namely Menggambik Tanah and Tabot Tebuang.